CLASSIFYING SPEECH ACT IN THE MOVIE TO ALL THE BOYS ALWAYS AND FOREVER - Yanti, Cita Hikmah; Ramadani, Wulan (Jurnal Ilmiah Bina Bahasa, 2023)
Language is a critical component of communication tools. People can form good relationships by communicating with one another. They must understand what the speaker says in order to communicate effectively. In this case, learning speech act theory is critical to addressing these issues. Speech acts are actions that can be performed through utterance. This study aims at analyzing types of speech act and the classifications of speech act in the movie To All The Boys Always and Forever. The writer used a descriptive method to analyze the data of this research. The descriptive method was applied in this research to analyze the utterances of the main character and the interlocutor through the transcriptions of the “To All The Boys Always and Forever” movie. The writer analyzed the data by categorizing the utterances of the main character by using John Searle’s theory then matching the meaning of context with the definitions of locutionary, illocutionary and, perlocutionary.The result in locutionary acts, there are 188 utterances that uttered by Lara Jean as a main character. In terms of illocutionary acts, representatives get the highest number of Lara Jean’s utterances which are up to 53.01% and, in terms of perlocutionary there are two acts which occured to Lara Jean’s utterances. They are to surprise the hearer and to get the hearer to do something.